ALMUDENA GRANDES AND JAVIER MARÍAS: TWO GENUINE AND UNREPEATABLE COLUMNISTS - Artemova , Lyudmila (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
In this study, we will focus on the columnism of Almudena Grandes and Javier Marías, two brilliant contemporary writers and undisputed Spanish stylists, in order to find the points of convergence and divergence in their idiostyles. Our article can be perceived as a small tribute to brilliant authors and true columnists, whose long and fruitful collaboration with “El País Semanal” was an important milestone both in their personal careers and a real pleasure for their loyal readers. Their columns were distinguished by originality and genuineness, sharpness of thoughts, positions, ideas, unique originality of their authorial styles. Their journalistic work is unique due to the refined and balanced style. Frank assessment combined with inherent emotionality – negative in the case of J. Marias' columns and more balanced in the case of A. Grandes – constitute another focus of attention. The subtle combination of styles, the peculiarity of their artistic prose, colored with "splashes" of colloquial style, unite the work of these unique and inimitable columnists, whose "opinion journalism" so captivated the readership. ___________References:• Cornejo-Parriego, «Genealogía esquisofrénica y la identidad nacional en Malena es un nombre de tango de Almudena Grandes.» Pluralidad narrativa: escritores españoles contemporráneos (1984-2004), Angeles Encinar, M. Glenn (Madrid: Biblioteca Nueva, 2013): 43-61.• García, “Javier Marías” 100 escritos del siglo XX. Ámbito hispánico. Coord. Domingo Ródenas (Barcelona: Ariel, 2008), 216.• Lampis, Estilística: Historias, conceptos, práctica (Granada: Comares, S.L., 2020), 157.• López Pan, La columna periodística. Teoría y práctica. El caso de hilo directo (Pamplona: Eunsa, 1996), 186.• Núñez Díaz, La colaboración de Javier Marías en la prensa. Opinión y Creación (Madrid, Editorial UNED, 2014), 424.• Grandes, Barrientos no quiere ser padre, 10/7/2016 https://elpais.com/elpais/2016/07/10/ eps/1468101926_146810.html• Grandes, Gangrena, 14/6/2021 https://elpais.com/opinion/2021-06-14/gangrena.html• Grandes, El aire de una mañana de primavera, 5/6/2021 https://elpais.com/eps/2021-06-05/el-aire-de-una-manana-de-primavera.html• Grandes, El futuro de Dani, 24/7/2016 https://elpais.com/elpais/2016/07/24/eps/ 1469311536_146931.html• Grandes, Lecciones del volcán, 24/10/2021 https://elpais.com/eps/2021-10-24/lecciones-del-volcan.html• Grandes, Rosas azules, 7/11/2021 https://elpais.com/eps/2021-11-07/rosas-azules.html• Grandes, Suyos eran los pájaros, 26/9/2021 https://elpais.com/eps/2021-09-26/suyos-eran-los-pajaros.html• Marías, ¿A quién podemos cargarnos hoy? 26/2/2017, https://elpais.com/elpais/2017/02/ 26/eps/1488063934_148806.html• Marías, Arrepentimiento simultáneo, 25/5/2021, https://elpais.com/eps/2021-05-02/ arrepentimiento-simultaneo.html• Marías, El cuento de Catherine el Biombo, 3 27/03/2022, https://elpais.com/eps/2022-03-27/cuento-de-catherine-del-biombo-3.html• Marías, Cuando los tontos mandan, 29/1/2017, https://elpais.com/elpais/2017/01/29/ eps/1485644725_148564.html• Marías, Cuento del profesor Pírfano, 4 7/5/2022, https://elpais.com/eps/2022-05-08/cuento-del-profesor-pirfano-4.html• Marías, Se supone que estudió, 26/12/2016, https://www.zendalibros.com/se-supone-estudio/
Keywords: author's column, idiostyle, evaluation, emotionality, expressive syntax